Unveiling the nongenomic actions of thyroid hormones in adult mammalian brain: The legacy of Mary B. Dratman - Chakrabarti, Nilkanta; Sarkar, Pradip K.; Ray, Arun K.; Martin, Joseph V. (Frontiers in Endocrinology, 2023)
A comprehensive review was conducted to compile the contributions of Mary B. Dratman and studies by other researchers in the field of nongenomic actions of thyroid hormones in adult mammalian brain.Dratman and her collaborators authored roughly half of the papers in this area. It has been almost fifty years since Dratman introduced the novel concept of thyroid hormones as neurotransmitters for the first time. The characterization of unique brain-region specific accumulation of thyroid hormones within the nerve terminals in adult mammals was a remarkable contribution by Dratman. It suggested a neurotransmitter-or neuromodulator-like role of thyroid hormone and/or its derivative, 3-iodothyronamine within adrenergic systems in adult mammalian brain. Several studies by other researchers using synaptosomes as a model system, have contributed to the concept of direct This is a provisional file, not the final typeset article nongenomic actions of thyroid hormones at synaptic regions by establishing that thyroid hormones or their derivatives can bind to synaptosomal membranes, alter membrane functions including enzymatic activities and ion transport, elicit Ca 2+ /NO-dependent signaling pathways and induce substrate-protein phosphorylation. Such findings can help to explain the physiological and pathophysiological roles of thyroid hormone in psychobehavioral control in adult mammalian brain. However, the exact mode of nongenomic actions of thyroid hormones at nerve terminals in adult mammalian brain awaits further study.